2006
DOI: 10.1177/030802260606900402
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Canadian Occupational Performance Measure: A Clinical Practice Perspective

Abstract: Occupational therapists working to a philosophy of client-centred practice will benefit from a reliable and well reviewed outcome measure to provide an evidence base. A systematic review of the literature was undertaken to evaluate worldwide publications on the use of the Canadian Occupational Performance Measure (COPM) to determine its impact on clinical practice in occupational therapy. A literature search strategy was deployed which resulted in a review of 64 articles. A themed analysis approach was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 64 publications
5
46
0
6
Order By: Relevance
“…The COPM is a client-centered standardized outcome measure that uses a semi-structured interview to identify and rate performance and satisfaction in self-identified problem areas on a 1-10 Likert scale (Law et al, 2005). A systematic review by Parker and Sykes (2006) reported that the COPM is responsive to change over time, shows positive effects with client-related factors, allows clients to name their own problems and generate client-centered goals, and allows therapists and clients to feel as if they are partners. Test-retest reliability of the COPM has been determined to be at .80 and above.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…The COPM is a client-centered standardized outcome measure that uses a semi-structured interview to identify and rate performance and satisfaction in self-identified problem areas on a 1-10 Likert scale (Law et al, 2005). A systematic review by Parker and Sykes (2006) reported that the COPM is responsive to change over time, shows positive effects with client-related factors, allows clients to name their own problems and generate client-centered goals, and allows therapists and clients to feel as if they are partners. Test-retest reliability of the COPM has been determined to be at .80 and above.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…O fato de o cliente apresentar déficits cognitivos é assinalado como uma limitação de uso da medida, já que sua habilidade de tomar decisões fica restrita (CLEwES, 2003;PAN et al, 2003;CARSwELL, 2004;PARkER;SYkES, 2006;CHATFIELD;BECkETT, 2007). Os terapeutas ocupacionais que aplicaram a COPM ressaltaram ainda a dificuldade de classificar alguns dos problemas identificados pelos clientes nas áreas de desempenho ocupacional que o instrumento aborda (PAN et al, 2003).…”
Section: Limitações Do Instrumentounclassified
“…Outra vantagem detectada por meio da aplicação da COPM diz respeito ao esclarecimento dos membros da equipe multidisciplinar sobre o papel do terapeuta ocupacional, repercutindo em encaminhamentos mais apropriados para essa modalidade de intervenção (wARREN, 2002;CRESSwELL;RUGG, 2003;CLEwES, 2003;CARSwELL, 2004;PARkER;SYkES, 2006). Tal vantagem pode contribuir para a minimização da incongruência entre a razão para se procurar o serviço, o procedimento de admissão, o serviço em si e seu resultado.…”
Section: Vantagens Do Instrumentounclassified
See 2 more Smart Citations